2009
DOI: 10.1080/09513590902730804
|View full text |Cite
|
Sign up to set email alerts
|

Repressive effect of the phytoestrogen genistein on estradiol-induced uterine leiomyoma cell proliferation

Abstract: These experimental findings in vitro show that the repressive effect of genistein on E(2)-induced ELT-3 cell proliferation is through the activation of PPARgamma. Genistein may be useful as an alternative therapy for leiomyoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…15,16 We selected a diet containing 600G and predicted that genistein would have advantageous effects on several markers of cardiovascular health. With this concentration of genistein in the diet, we routinely obtain plasma genistein levels of 7.7±4.0 µmol/L and 4.2±2.3 µmol/L in intact female and male mice, respectively, 12 indicating that continuous consumption of genistein can result in sustained plasma levels in the low µmol/L ranges.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 We selected a diet containing 600G and predicted that genistein would have advantageous effects on several markers of cardiovascular health. With this concentration of genistein in the diet, we routinely obtain plasma genistein levels of 7.7±4.0 µmol/L and 4.2±2.3 µmol/L in intact female and male mice, respectively, 12 indicating that continuous consumption of genistein can result in sustained plasma levels in the low µmol/L ranges.…”
Section: Discussionmentioning
confidence: 99%
“…There is a concern that the isoflavones may mimic this action of estrogen [56]. However, a recent study on estrogen proliferation of ELT-3s cell also showed that genistein blocked this action of 17 β -estradiol [57]. Importantly, genistein's inhibitory effect was in turn attenuated by the PPAR γ inhibitor GW9662 [57].…”
Section: Association With Chronic Diseases: Cellular and Animal Momentioning
confidence: 99%
“…However, a recent study on estrogen proliferation of ELT-3s cell also showed that genistein blocked this action of 17 β -estradiol [57]. Importantly, genistein's inhibitory effect was in turn attenuated by the PPAR γ inhibitor GW9662 [57]. This underscores the likelihood that the action of isoflavones in mammals including man is multi-factorial and that PPAR signaling is a target of the isoflavones.…”
Section: Association With Chronic Diseases: Cellular and Animal Momentioning
confidence: 99%
See 1 more Smart Citation
“…In endometrial adenocarcinoma (Ishikawa) cells, both genistein and estrogen upregulated ER-stimulated gene activity and decreased estrogen-induced proliferation and stromal ER-β cell activation [185,186]. Genistein has suppressive effects on E2-stimulated ELT-3 cell proliferation in ELT-3 cells (uterine leiomyoma cell line) through PPARγ activation [187].…”
Section: Genital Cancersmentioning
confidence: 99%